Growth Forms of Macrophytes in Salona Tal and its Adjoining Wetlands of Uttar Pradesh - SANTOSH KUMAR,; SATYA NARAIN, (International Journal of Pharma and Bio Sciences, 2010)
Salona Tal with their wetlands has large eutrophic water body spread over 4234 sq. km. During the survey 193 angiosperm species belonging to 118 genera of wetland and aquatic macrophytes with rare species e. g. Centrostachys aquatica, Alternanthera philoxeroides, Neptunea oleracea etc. are reported and classified according to their growth forms and enumerated with their diversity, growth form and phenology. Current status and conservation measure are also reported in this paper.